Parametric Analysis of Horizontal Static and Dynamic Behavior in Different Types of Masonry Structures - Georgios Xekalakis; Dimitris Pitilakis; Giulio Zuccaro; Petros Christou (Civil Engineering Journal, 2023)
This article introduces the "Pre-seismic Survey Form for Masonry" (PRISM), a simplified tool for evaluating masonry structures. It aims to be user-friendly for both experienced surveyors and beginners. The primary objective is to develop PRISM as an efficient means of gathering relevant data that influences the diverse behaviors exhibited by masonry structures, covering both structural and non-structural aspects. PRISM's development involves a parametric method for identifying critical parameters by analyzing drift results from the response spectrum and horizontal static analyses. These analyses are performed on common masonry structures in European Mediterranean nations. The study investigates various factors, including facade openings, materials around openings, wall thickness, ground type, ground acceleration (g), and principal structural material. By examining 300 2D models created in SAP2000, correlations in structural responses are established. The findings of the parametric analysis significantly enrich the qualitative and quantitative comprehension of structural responses. This advancement contributes to the contemporary knowledge of prevalent masonry structures within European Mediterranean regions. The PRISM survey form employs a numeric rating scale format. Notably, PRISM enables surveyors to access field results, minimizing reliance on computers quickly. The form's design also ensures accessibility and data reliability, making it universally applicable while maintaining simplicity. Doi: 10.28991/CEJ-2023-09-10-015 Full Text: PDF